Birth and adoptive parent anxiety symptoms moderate the link between infant attention control and internalizing problems in toddlerhood. (28th January 2014) - Brooker, Rebecca J.; Neiderhiser, Jenae M.; Ganiban, Jody M.; Leve, Leslie D.; Shaw, Daniel S.; Reiss, David
Abstract Attention control plays an important role in the development of internalizing symptoms in children. We explored the degree to which infants' genetic and environmentally based risk moderated the link between attention control and internalizing problems during toddlerhood. These associations were examined within a prospective adoption design, enabling the disentanglement of genetic and environmental risk for internalizing problems. Attention control in adopted infants was observed during periods of distress at age 9 months. Birth parents' anxiety symptoms were used as an index of genetic risk, while adoptive parents' anxiety symptoms were used as an index of environmental risk. Adoptive mothers and fathers reported on children's internalizing problems when children were 18 and 27 months old. Greater attention control in infancy appeared to mitigate genetically based risk for internalizing problems during toddlerhood when children were raised by adoptive parents who were low in anxiety. Findings suggest that for genetically susceptible children who are raised in low-risk environments, attention control may provide a protective factor against developing internalizing problems across early life.